MENGIDENTIFIKASI AKAR MASALAH DAN POLA KONFLIK PERWAKAFAN DI KABUPATEN PONOROGO - Huda, Miftahul (JURNAL TAPIS, 2012)
AbstrakThis research focuses on the legal conflict of endowment (waqaf), property donated for religious use. It deals with two problems namely, first, what kind of legal conflict of waqaf occured in Sakinah Village Foundation of ponorogo? And second, what is the pattern and the mode of the legal conflict of endowment? A case study research was applied to figure out the the answer of the questions. The research findings show that the conflict root of the legal conflict of endowment in Sakinah Village-Mawaddah 3 is the differences in terms of understanding on waqif and the endowment law, the internal problems within the nazhir, and the unfinished or uncertain status of the land endowment. Meanwhile, the pattern and the mode of the legal conflict of endowment within the Sakinah Village Foundation is miscommunication pattern between the nazhir and the waqif, the unprofessional of nazhir, in term of capacity and institution, in managing the endowment, and the unclear normative pattern of the endowment status. Those three patterns of endowment conflict is due to the interest conflict mode in âusurping and manageing the endowment assetâ between the waqif and the nazhir. Keywords: Conflict. endowment, mauqÃ»f âalaih, wÃ¢kif, sakinah village foundation.